Iranian women's self-concept after hysterectomy: A qualitative study - Fatemeh Goudarzi; Talat Khadivzadeh; Abbas Ebadi; Raheleh Babazadeh (Wolters Kluwer Medknow Publications, 2021)
Background: The loss of female organs leads to profound changes in one's perception of oneself. There is limited information about the impact of hysterectomy on women's self-concept and culture. Therefore, this study was conducted with the aim to deepen our understanding of the self-concept of Iranian women after hysterectomy. Materials and Methods: This qualitative study was conducted using directed content analysis approach. The participants included 30 women with a history of hysterectomy who were selected through purposive sampling method. Data were collected from August 2018 to November 2019 using in-depth and semi-structured interviews based on the self-concept mode of the Roy Adaptation Model (RAM) in Mashhad, Iran. Data analysis was performed using the deductive approach of Elo and Kyngäs in MAXQDA software. Results: As a result of the analysis of the interviews, the main category of "incoherent cognition of self-concept" emerged, which included the two generic categories of "heterogeneous feelings toward and imaginations of the body" and "changed self-perception", and five subcategories. Conclusions: Women's self-concept changed after hysterectomy in both its physical and psychological aspects. Therefore, counseling before and after hysterectomy is recommended to improve women's self-concept after hysterectomy.